The surgical treatment of ascending aortic aneurysms associated with aortic valve disease - Fernández Perdomo, Gonzalo; Goller, Wolfgang; Burstin, Jacobo; Lorenzo, Alvaro; Nozar, José V.; Estable, Héctor; Abó, Juan C. (Cirugía del Uruguay, 1982)
The authors present the experience achieved at the Heart Surgery Department of the "Clínicas Hospital" with patients with aneurysm of the ascending aorta and aortic insufficiency. A patient was surgically explored and died suddenly while awaiting his reoperation. A patient who underwent valvular replacement and aneurusmoraffia, died in the postoperative for the strong deterioration of his myocardial function. A patient was operated on replacing his aortic valve and the ascending aorta in its supracoronary portian, protecting him with cardiac paralysis; the near and distant evolution was good. It is currently considered that these patients are to be surgically treated in our enviroment. The surgical technique will depend upon the degree of involvement of the aortic wall in each particular case. The valvular prostheses will be mechanical; since a high rate of dysfunction has been observed with the use of some biological valves in our enviroment. A periodical control with aortography is recoended for an early recognition of the postoperative local complications.